EFFECT OF FLAXSEED ENRICHMENT ON QUALITY ATTRIBUTES OF RABBIT MEAT AND MEAT PRODUCT - M. R. Tariq; M. I. Khan; A. Sameen; M. Nisa (Journal of Animal and Plant Sciences, 2016)
Rabbit is reared in rural areas of Pakistan under backyard farming system for local consumption to get meat and fur. Quality characteristics of rabbit meat make it more nutritious with game animal taste, light flavor and also with firmer meat texture. For improvement of nutritional profile, fatty acid composition, the current study was carried out to investigate the dietary responses of flaxseed from 3.5 – 7 %. The treatment plan was as (T0 = control feed, T1 = 7 % flaxseed/kg feed, T2 = 3.5 % flaxseed/kg feed). Growth parameters like weight gain and feed intake were significantly increased by dietary supplementation of flaxseed. The rabbits fed on 7 % level of linseed gained maximum weight while the lowest body weight gain was found in rabbits fed on control (T0). The FCR was found significantly higher in rabbits fed on control (T0) and lowest FCR was found in broilers fed on 7 % linseed (T3). Poly unsaturated fatty acid ratio was higher over saturated fatty acid in T1 as compared to other supplemented group. The poly unsaturated fatty acids were observed significantly higher in loin and hind leg meat of rabbits fed on 7 % linseed (T1). The nuggets made from meat of group fed on highest level of linseed 7 % (T3) showed higher pH with storage intervals, higher water activity, higher color values and texture. Sensory evaluation was carried out by applying nine point hedonic scales by trained panelist who preferred loin rabbit nuggets of T1 which showed highest acceptance to consumer having light flavor and nice appearance
Keywords: Rabbit; rabbit meat; flaxseed enrichment; n-3 PUFA; rabbit meat nuggets